Relación en el largo plazo y causalidad entre emisión de CO2, consumo energético y crecimiento económico en el Perú 1995-2019 - Luna Farias, Anthony Paul (2023)
This research proposes to analyze the dynamic and causal relationship between electricity consumption, economic growth and carbon dioxide emission in Peru during the period 1995-2019. Based on a Autoregressive Vector Model (EVC), Johansen’s Cointegration and Granger’s Causality tests were used, considering as independent variables the consumption of electricity per capita (EC), Gross Domestic Product per capita (GDP) and carbon dioxide emission per capita (CO2) emissions as independent variables. The results suggest a long-term equilibrium relationship between CO2 emissions, economic growth and electricity consumption, as well as a one-way causal relationship that ranges from economic growth in Peru to CO2 emissions, but not in the sense of electricity consumption. This suggests that Peru is in a scenario of neutrality, that is, public policies aimed at preserving or expanding electricity consumption would not decisively affect economic growth, and vice versa.